Brutality in Han Kang's Novel Human Acts (2014) - Titiek Prihatiningsih; Desvalini Anwar (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue of brutality in novel Human Acts (2014) by Han Kang. It is also intended to find out how the implied author contributes in revealing the issue of brutality. This analysis is related to concept of Power Relation by Michel Foucault that is supported by the text and context-based interpretation. The result of the analysis shows that the brutality that is committed by military government in maintaining their domination done through two strategies: enforcing regulations and utilizing state apparatus.